Effect of Happy Work Environment on Innovative Work Behaviours: Analytical Research in the Ministry of Higher Education and Scientific Research - Hasan Ghafil Jawad Al Issawi; Ali Hassoon Altaee (Eximia, 2024)
The current research aims to test the effect of a happy work environment on Innovative work behaviors, as a stratified random sample of (328) employees of the departments of the Ministry of Higher Education and Scientific Research was selected from the study population of (2229). Relying on the questionnaire in collecting data, the questionnaires suitable for statistical analysis were (322) questionnaires, as the happy work environment variable includes five dimensions: (credibility, respect, fairness, pride, true friendship), while the Innovative work behavior variable dealt with four dimensions (ability Providing Innovative solutions to problems, the ability to come up with new ideas and proposals, change, initiative, and the spirit of risk), and the idea of ​​the research revolves around providing a happy work environment that contributes to and supports Innovative work behaviors. The researcher used several statistical methods to analyze the questionnaire results, including a simple linear regression coefficient. Simple and descriptive analysis using the program (SPSS.v23, AMOS.v23), and the hypotheses were proven correct by finding an effect of a happy work environment in its dimensions on Innovative work behavior in its dimensions. A set of results has also been reached, among which are doubts or concerns about the reliability of management information and procedures, as well as some gaps or deficiencies in the control processes and the audit system, it appears that the responsible management is not at a good level in managing work and fulfilling commitments and promises towards its employees, as well as being informed. On issues and tasks related to work, and from this perspective it is due to several reasons, including the managerial skills possessed by managers that are not sufficient or inconsistent with the specialty of the work assigned to them, and that management capabilities are limited and rely on performing their tasks in a normal or average manner without skill or exceptionality.